2016
DOI: 10.1038/srep19367
|View full text |Cite
|
Sign up to set email alerts
|

A graphene oxide/amidoxime hydrogel for enhanced uranium capture

Abstract: The efficient development of selective materials for the recovery of uranium from nuclear waste and seawater is necessary for their potential application in nuclear fuel and the mitigation of nuclear pollution. In this work, a graphene oxide/amidoxime hydrogel (AGH) exhibits a promising adsorption performance for uranium from various aqueous solutions, including simulated seawater. We show high adsorption capacities (Qm = 398.4 mg g−1) and high % removals at ppm or ppb levels in aqueous solutions for uranium s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(67 citation statements)
references
References 52 publications
2
65
0
Order By: Relevance
“…Compared with microporous and fiber‐based amidoxime‐functionalized adsorbents, hydrogel‐based polymeric adsorbents, which do not require expensive instruments and tedious processes, exhibit a loose hydrophilic 3D network containing lots of water that can effectively disperse the amidoxime‐functionalized polymers. Therefore, the uranyl ions can easily immigrate into the inner layer of the hydrogel . While other hydrogel‐based adsorbents have high uranium adsorption capacities or good selectivity, amidoxime‐functionalized hydrogels have both .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with microporous and fiber‐based amidoxime‐functionalized adsorbents, hydrogel‐based polymeric adsorbents, which do not require expensive instruments and tedious processes, exhibit a loose hydrophilic 3D network containing lots of water that can effectively disperse the amidoxime‐functionalized polymers. Therefore, the uranyl ions can easily immigrate into the inner layer of the hydrogel . While other hydrogel‐based adsorbents have high uranium adsorption capacities or good selectivity, amidoxime‐functionalized hydrogels have both .…”
Section: Methodsmentioning
confidence: 99%
“…However, to improve the hydrophilicity of the poly(amidoxime) (PAO) and other amidoxime‐functionalized polymers, additional hydrophilic hydrogel 3D networks are commonly introduced. These additional networks account for the high weight percentages of the adsorbents . But the low weight percentages (typically no greater than 50 wt%) of the amidoxime‐functionalized polymers seriously limits the uranium adsorption capacity of the hydrogels .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] In spite of its apparent chemical inertness, UO 2 2+ has recently caught growing attention for the tantalizing prospect of activating its remarkably stable metal-oxygen double bonds. 6 Nevertheless, the activation and functionalization of UO 2 2+ still remain challenging and elusive.…”
Section: +mentioning
confidence: 99%
“…Meanwhile, it also could be found that the peak of N 1 s shifted from 399.98 eV to 400.13 eV, which confirmed the decrease in electron density for the oxygen and nitrogen atoms. It could be deduced that the lone pairs of nitrogen atom and oxygen atom were donated to the UO 2 2+ center to form a stable chelate …”
Section: Resultsmentioning
confidence: 99%